(untitled) (Research, Society and Development, 2022)
Objective: To identify in the scientific literature nursing care that is regularly omitted and the reasons for this omission in hospital units. Methods: Integrative review whose literature search was carried out from March to July 2022, by consulting five databases: MEDLINE, LILACS, CINAHAL, EMBASE and SCOPUS. The research question was based on the PICO strategy in which the problem was “omission of care”, the phenomenon of interest was the “reasons for omission” and the context was “nursing care”. The inclusion criteria were: full articles related to the research object, without language restrictions, originating from national and international journals, indexed in the aforementioned databases and without time limitation. Results: Among the productions found, 20 articles were selected that passed the sieve of inclusion and exclusion criteria, based on the theme “omitted nursing care and its reasons”. Conclusion: It was evidenced that nursing care that is regularly omitted contributes negatively to the quality of care offered to the health user and to the job satisfaction of nursing professionals.